2019
DOI: 10.1590/1807-1929/agriambi.v23n9p662-668
|View full text |Cite
|
Sign up to set email alerts
|

Water relations in parsley plants cultivated in brackish nutrient solutions of different cationic natures

Abstract: The analysis of plant response to the cationic variability of the waters, in addition to the osmotic component, is indispensable in the context of salt stress. Thus, between October 2017 and February 2018, in Recife, PE, Brazil (8° 1’ 7” S and 34° 56’ 53” W, and altitude of 6.5 m), the present study was carried out to evaluate the water relations of parsley plants (Petroselinum crispum), cv. Graúda Portuguesa, cultivated in brackish nutrient solutions (electrical conductivities of 1.7, 2.7, 3.7, 4.7, 5.7 and 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 17 publications
(20 reference statements)
3
10
0
Order By: Relevance
“…Gains in the production of fresh and dry biomass in coriander plants with the increase in the concentration of salts were also verified by Martins et al (2019), who also found that the prevalence of Na + , Ca 2+ , and Mg 2+ impacts differently (p ≤ 0.05) the SFM of parsley with increasing concentration.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…Gains in the production of fresh and dry biomass in coriander plants with the increase in the concentration of salts were also verified by Martins et al (2019), who also found that the prevalence of Na + , Ca 2+ , and Mg 2+ impacts differently (p ≤ 0.05) the SFM of parsley with increasing concentration.…”
Section: Resultsmentioning
confidence: 65%
“…Analysis of chlorophyll fluorescence, CO 2 internal concentration, instantaneous carboxylation efficiency, and CO 2 assimilation rate helps to understand the limitations imposed by salinity on gas exchange (Shoukat et al, 2019) and on the photosynthetic process (Martins et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In parsley plants exposed to different cationic natures there are changes in production (Martins et al, 2019b), water relationships (Martins et al, 2019a), and photochemical efficiency (Martins et al, 2020). However, studies that address aspects of use efficiency and relationships between nutrients are still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Some regions usually undergo water shortages, such as the Semiarid region of the Northeast of Brazil, where agricultural crops are often grown using irrigation with underground brackish waters (Albuquerque et al, 2015). The need of using technologies compatible to this situation is evident in these regions (Paulus et al, 2012;Silva Júnior et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, despite NFT hydroponics is used for crops that are relatively tolerant to salt stress, such as cauliflower (Giuffrida et al, 2016), it presents specificities regarding the use of brackish waters that still require studies. These specificities include the frequency and flow rate of the circulation of the nutrient solution (Silva Júnior et al, 2019;Soares et al, 2020), and the chemical composition of the waters used for the crops (Martins et al, 2019).…”
Section: Introductionmentioning
confidence: 99%